ZNO and AG-ZNO crystals: synthesis, characterization, and application in heterogeneous photocatalysis - Lucilha, Adriana Campano; Silva, Marcelo Rodrigues Da; Ando, Rômulo Augusto; Dall'antonia, Luiz Henrique; Takashima, Keiko (Sociedade Brasileira de Química, 2016)
ZnO and Ag-ZnO were synthesized in a simple and efficient manner by thermal decomposition of zinc oxalate and silver/zinc mixed oxalate. The influence of the addition of metallic silver on ZnO particles and the effect of temperature in the thermal treatment were investigated. The samples were characterized by thermogravimetric analysis, Raman, X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy, specific surface area (Brunauer-Emmett-Teller) and diffuse reflectance spectroscopy. The photocatalytic activity of these materials in the decolorization of direct red 23 diazo dye was studied. The complete conversion into oxides from oxalates at lower temperatures was determinant in the photocatalytic efficiency of both the oxides. The presence of silver in zinc oxide, treated at 400 °C, more than doubled the rate constant of diazo dye decolorization (6.87×10-3 min-1) with respect to ZnO, treated at 600 °C, resulting in 3.07×10-3 min-1 under UV irradiation at 30 °C.
Keywords: oxide semiconductor; surface modification; thermal treatment; direct red 23